2016
DOI: 10.5937/fizkul1601034t
|View full text |Cite
|
Sign up to set email alerts
|

The neuromechanical functional contractile properties of the thigh muscles measured using tensiomyography in male athletes and non-athletes

Abstract: Велимир Јекнић, ¹Универзитет у Београду, Факултет спорта и физичког васпитања ²Криминалистичко-полицијска академија, Земун Сажетак Невољне неуромеханичке контрактилне карактеристике мишића, нарочито мишића опружача и прегибача зглоба колена као највећих мишићних група каудалног дела тела, имају важну улогу како у свакодневном кре-тању тако и у спорту. На основу тих података могу се добити важне информације о функционалним каракте-ристикама мишића. Основни начин за процену функционалних невољних неуромеханичких… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(53 reference statements)
3
3
0
1
Order By: Relevance
“…It suggests that differently physically active individuals generally have similar levels of muscle stiffness and muscle Vc; at the same time, their levels of twitch force generation speed, muscle responsiveness, and muscle fiber composition are different. These results are in accordance with several previous studies that emphasized the differences in some TMG parameters between differently trained subjects (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…It suggests that differently physically active individuals generally have similar levels of muscle stiffness and muscle Vc; at the same time, their levels of twitch force generation speed, muscle responsiveness, and muscle fiber composition are different. These results are in accordance with several previous studies that emphasized the differences in some TMG parameters between differently trained subjects (30,31).…”
Section: Discussionsupporting
confidence: 93%
“…The findings from the present study show that male professional soccer players have shorter Tc values compared to a sample of the general population who had their RF rectus femoris muscle assessed using TMG. 43 This concurs with Toskic et al, (2016) 44 who reported lower Tc values in the vastus lateralis and the RF muscles of multi-sport athletes relative to aged matched in-active controls. When comparing our study findings to other sporting disciplines, professional soccer players had lower Dm and a lower Tc in the BF muscle relative to elite gymnasts 45 and male triathlon competitors.…”
Section: A Significant Difference Between Midfielders and Forwards Fo...supporting
confidence: 84%
“…Regarding the results obtained in non-athletes (Toskić, Dopsaj, Koropanovski, & Jeknić, 2016) it has been determined that their values were higher in Tc, and lower in the Dm variable in relation to our study. The results have indicated that there is a greater muscle stiffness determined in the recreational players, as well as a longer time required for the realization of the 90% complete muscle contractions.…”
Section: Discussionsupporting
confidence: 55%